Effect of lanthanum oxide additive on the sinterability, physical/mechanical, and bioactivity properties of hydroxyapatite-alpha alumina composite - SALMAN, SERDAR; PAZARLIOĞLU, SÜLEYMAN SERDAR (SPRINGER, 2019)
The aim of this study was to evaluate the effect of lanthanum oxide (La2O3) additive on the microstructural, physical, mechanical, and in vitro bioactivity properties of hydroxyapatite (HA)-alpha alumina (alpha-Al2O3) composite. The monolithic HA as well as composites of HA-5 wt% alpha-Al2O3 and HA-5 wt% Al2O3-(0.5 wt%, 1.5 wt%, and 2.5 wt%) La2O3 were uniaxially pelleted at 350 MPa with a size of null 11 and 11 mm(2) and sintered at the temperatures ranging from 1100 to 1300 degrees C for 4 h. The highest mechanical strength values of 130.20 +/- 6.22 MPa, 60.27 +/- 9.93 MPa, and 0.96 +/- 0.05 MPa m(1/2) for compressive strength (sigma(compressive)), three-point bending strength (sigma(three-point bending)), and fracture toughness (K-ic) were obtained for monolithic HA, respectively. While the decomposition (transformation of HA to secondary phases such as beta-tricalcium phosphate (beta-TCP), alpha-tricalcium phosphate (alpha-TCP), and calcium oxide (CaO)) ratio was about 5.7% for monolithic HA, it attained to 27.4% for HA-5wt% alpha-Al2O3 composite. However, addition of La2O3 to HA-5 wt% alpha-Al2O3 composite contributed to decreasing of decomposition from 27.4 to 22.0%. The mechanical strength values of sigma(compressive) of 214 +/- 32.50 MPa, sigma(three-point bending) of 75.70 +/- 2.40 MPa, and K-ic of 1.95 +/- 0.10 MPa m(1/2) were obtained for HA-5wt% alpha-Al2O3 composite. SEM images exhibited that alpha-Al2O3 led to decreasing the in vitro bioactivity of HA. However, La2O3 additive contributed to improvement of the mechanical as well as bioactivity properties of HA-5 wt% alpha-Al2O3 composite. HA-5 wt% alpha-Al2O3-0.5 wt% La2O3 composite can be used as a bioceramic in human body, because it has enough mechanical properties as well as its desirable in vitro bioactivity.
Keywords: Hydroxyapatite; Alpha-alumina; Lanthanum oxide; Sintering; MECHANICAL-PROPERTIES; BIOLOGICAL-PROPERTIES; PHASE-STABILITY; FABRICATION; POWDER; LA; TEMPERATURE; SCAFFOLDS; TOUGHNESS; PRESSURE